2007
DOI: 10.4161/cc.6.23.5018
|View full text |Cite
|
Sign up to set email alerts
|

TLR8: An Innate Immune Receptor in Brain, Neurons and Axons

Abstract: AbbReViATionSIκBα nuclear factor of κ light polypeptide gene enhancer in B-cells inhibitor α IRAK interleukin-1 receptor-associated kinase LPS lipopolysaccharide MyD88 myeloid differentiation factor 88 NFκB nuclear factor-κB PAMPs pathogen-associated molecular patterns TLR Toll-like receptor AcKnowLedgeMenTSWe thank colleagues I. Chiu, J. Lu, and J. Sloane for critical reading of the manuscript. This work was supported by grants from the US National Institutes of Health and the National Multiple Sclerosis Soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(83 citation statements)
references
References 97 publications
2
80
1
Order By: Relevance
“…Thus, cells in the CNS appear to be activated via TLR8 by ligands that are not of bacterial origin but that are induced during injury, autoimmune situations, hypoxia, and neurodegeneration (Kielian, 2006;Ma et al, 2007). Moreover, TLR8 stimulation has been associated with suppression of neurite outgrowth and induction of apoptosis.…”
Section: Synaptic and Nonsynaptic Communicationmentioning
confidence: 96%
“…Thus, cells in the CNS appear to be activated via TLR8 by ligands that are not of bacterial origin but that are induced during injury, autoimmune situations, hypoxia, and neurodegeneration (Kielian, 2006;Ma et al, 2007). Moreover, TLR8 stimulation has been associated with suppression of neurite outgrowth and induction of apoptosis.…”
Section: Synaptic and Nonsynaptic Communicationmentioning
confidence: 96%
“…MR imaging features of human parechovirus include punctate high-signal-intensity white matter lesions on T1-weighted images and symmetric foci of restricted diffusion in the subcortical white matter, corpus callosum, optic radiation, internal capsule, and cerebral peduncles on diffusion-weighted images (30) (Fig 25). In the presence of a parechovirus infection, inflammatory cytokines that are toxic to premyelinating oligodendrocytes and developing axons may be secreted by microglia (31).…”
Section: Imaging-based Differential Diagnosis Of Neonatal Encephalopathymentioning
confidence: 99%
“…Neurological deficits manifest clinically in EAE mice at approximately the same time as characteristic SMI32+ spheroids are detectable in spinal cord axons ( Figure 6, Soulika et al, 2009). These spheroids contain high concentrations of Toll-like receptor 8 (TLR8) protein (Soulika et al, 2009) shown to cause neuronal death via apoptosis and inhibit neurite formation (Ma et al, 2006(Ma et al, , 2007. In this same EAE model, innate immunity infiltrates are detectable early on in the disease course.…”
Section: Wallerian Degenerationmentioning
confidence: 80%